Mitigation of thermal noise in GRACE accelerometer observations. Issue 1 (1st January 2022) - McGirr, Rebecca; Tregoning, Paul; Allgeyer, Sebastien; McQueen, Herb; Purcell, Anthony
Abstract: The precise calculation of GRACE and GRACE-FO satellite orbits is reliant on knowledge of accurate non-gravitational accelerations acting on the spacecraft. These are measured by the on-board accelerometers that require a thermal environment stabilised to ∼ ± 0.1 °C per revolution. However, during periods of the GRACE mission with reduced thermal control, internal temperature variations reached up to 10 °C within a revolution, causing low-frequency and non-linear drifts in the accelerometer observations. Additionally, accelerometer bias drifts occurred throughout the GRACE mission as changes in the orientation of the orbital plane with respect to the Earth-to-Sun vector caused the satellites to absorb more or less solar energy. These temperature-induced drifts degrade the quality of mass change estimates, particularly during the latter half of the GRACE mission after thermal control of the satellites was terminated. We filter (in the frequency domain) the accelerometer observations to remove these low-frequency components ( f < 0.045  mHz). The bias drift removed from the cross-track is then scaled to derive a thermally-based correction for the highly sensitive along-track observations. We then estimate temporal gravity fields using the ANU GRACE software, our filtered accelerometer observations and the range acceleration as the inter-satellite observation. The use of our thermally-corrected accelerometer measurements significantly improves the accuracy of both orbit modelling and gravity field estimation.